Effects of Therapeutic Ultrasound on Pain, Disability, Walking Performance, Quality of Life, and Depression in Patients with Chronic Low Back Pain: A Randomized, Placebo Controlled Trial - Dilek Durmuş; Yeşim Akyol; Kıvanç Cengiz; Tülay Terzi; Ferhan Cantürk (Archives of Rheumatology, 2010)
Objective: The aim of the current study was to evaluate the effects of therapeutic ultrasound on pain, disability, walking performance, quality of life (QOL) and depression in patients with chronic low back pain (CLBP). Materials and Methods: Forty-two patients with CLBP were randomly allocated into two groups. Patients in group 1 received therapeutic ultrasound, exercise, and hot packs, while patients in group 2 received sham ultrasound, exercise, and hot packs. All treatment programs (ultrasound, sham ultrasound, hot packs, and exercise) were performed 5 days a week for 3 weeks. Patients were evaluated by the following parameters: pain (visual analog scale [VAS]), disability (Modified Oswestry Low Back Pain Disability Questionnaire and Pain Disability Index), functional performance (6-Minute Walk Test [6MWT]), QOL (Short Form 36 [SF-36]), and depression (Beck Depression Inventory [BDI]). Results: A significant improvement was noted in both groups in pain, disability, walking performance, QOL and depression after treatment. Significantly greater improvement was observed in group 1 compared to group 2 in pain, emotional and physical role functioning, functional performance, and depression. Conclusion: Therapeutic ultrasound was shown to be effective on pain, some particular parameters of QOL, functional performance, and depression in patients with CLBP. (Turk J Rheumatol 2010; 25: 82-7)